Pengaruh Intergrated Marketing Communication terhadap Citra Dodol Picnic sebagai Makanan Khas Kota Garut - Apit Buchori; Ronny Sugiantoro (Ideas Publishing, 2023)
Many companies do not understand about integrated marketing communication that can affect brand image. This research is to test the brand image of the Dodol Picnic brand produced by PT. Herlinah Citra Pratama which can be influenced simultaneously by integrated marketing communication. The method used by researchers using quantitative data analysis was processed with the IBM SPSS version 22 software program with a descriptive method. The results show that it has implemented its communication strategy through several advertising, sales, promotion, public relations, events and direct marketing activities. This simultaneously has a positive influence on brand image, the greater the integrated marketing communication, the more significant it will strengthen the brand image. Improving the brand image of Dodol Picnic, the company s icon production.